2020
DOI: 10.1515/med-2020-0404
|View full text |Cite
|
Sign up to set email alerts
|

Pericentric inversion in chromosome 1 and male infertility

Abstract: AbstractPericentric inversion in chromosome 1 was thought to cause male infertility through spermatogenic impairment, regardless of the breakpoint position. However, carriers of pericentric inversion in chromosome 1 have been reported with normal fertility and familial transmission. Here, we report two cases of pericentric inversion in chromosome 1. One case was detected in utero via amniocen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Although some cases with inversion of chromosome 10 show normal fertility, these carriers have a higher reproductive risk. For structural reorganization carriers, the mechanism of chromosomal abnormality affecting spermatogenesis includes the following: (1) an interchromosomal effect increases the risk of numerical chromosomal abnormalities in the gametes, (2) disturbance of chromosomal pairing, synapsis, and recombination during meiosis, (3) DNA fragmentation in spermatozoa and activation of apoptosis, and (4) interference of specific gene function at the breakpoint [ 4 , 20 ]. However, Young et al [ 7 ] reported that infertile carriers with chromosomal inversions are not susceptible to an interchromosomal effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some cases with inversion of chromosome 10 show normal fertility, these carriers have a higher reproductive risk. For structural reorganization carriers, the mechanism of chromosomal abnormality affecting spermatogenesis includes the following: (1) an interchromosomal effect increases the risk of numerical chromosomal abnormalities in the gametes, (2) disturbance of chromosomal pairing, synapsis, and recombination during meiosis, (3) DNA fragmentation in spermatozoa and activation of apoptosis, and (4) interference of specific gene function at the breakpoint [ 4 , 20 ]. However, Young et al [ 7 ] reported that infertile carriers with chromosomal inversions are not susceptible to an interchromosomal effect.…”
Section: Discussionmentioning
confidence: 99%
“…Chromosomal disorders are considered to be an important genetic factor leading to defects of spermatogenesis. Chromosomal inversion and its breakpoint are closely related to male infertility [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nineteen individuals had non-mosaic Klinefelter syndrome (47,XXY), nine had AZF microdeletions (seven AZFc microdeletions; two AZF b and c microdeletions), one had translocation (20;22)(q11.2;p11.1) [14], and one had inversion (1)(p22q44) [15].…”
Section: Genetic Spermatogenic Failure (N = 30)mentioning
confidence: 99%
“…Male infertility is a common clinical problem in urological practice, and is a pathological condition with a genetic background. [ 1 ] Chromosomal aberration is reported to one of the common causes in infertile men, [ 2 ] and is detected in 14% of infertile patients. [ 3 ] Reciprocal balanced translocation is one of the most frequently occurring human chromosomal abnormalities.…”
Section: Introductionmentioning
confidence: 99%